Critical Oscillation Constant for Euler Type Half-Linear Differential Equation Having Multi-Different Periodic Coefficients - Adil Misir; Banu Mermerkaya (International Journal of Differential Equations)
We compute explicitly the oscillation constant for Euler type half-linear second-order differential equation having multi-different periodic coefficients.